(untitled) - Turcotte, Donald Lawson (Cambridge,New York, 2002)
Geodynamics provides the fundamentals necessary for an understanding of the workings of the solid earth, describing the mechanics of earthquakes, volcanic eruptions, and mountain building in the context of the role of mantle convection and plate tectonics. Observations such as the earth's gravity field, surface heat flow, distribution of earthquakes, surface stresses and strains, and distribution of elements are discussed
Keywords: Geodynamics,Địa chất học